Essentials of Dreamweaver 4 : skills and drills training. - Siegel, Kevin A., ....- (Riva : IconLogic, 2001)
Samenvatting:This book has been designed to quickly teach you all of the essentialskills necessary to work with this fantastic web page development tool.You will learn how to define sites, format text using cascading stylesheets, use the new Design View to create tables, use the Historypalette, import text into a table and format tables, create templates,use libraries, create and work with online forms, create and use frames,add animation and even FTP your completed files to your Internet ServiceProvider.
Keywords: Elektronisch publiceren; Programmatuurontwikkeling; Www world wide web